PENERAPAN GAYA PENYUTRADARAAN HITCHCOCKIAN DALAM FILM PENDEK THRILLER UNPAID SOULS - Diputra, Komang Purna; Payuyasa, I Nyoman; Pandet, Putu Raditya (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
With digital money, e-wallets, and online platforms, gambling has become increasingly accessible to teenagers, leading to conflicts like fights, theft, and even murder, often driven by debt and verbal abuse. Film, as a visual narrative medium, effectively highlights these issues. The author presents a thriller short film about a gambler facing significant loss, directed in Hitchcock’s suspenseful style, known for its psychological depth and innovative cinematography. This film critiques the negative impacts of gambling by combining narrative, symbolism, and visuals to deliver a socially relevant message, emphasizing the dangers of gambling and its profound consequences.